2020
DOI: 10.1016/j.eats.2020.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Meniscus Replacement Using Peroneus Longus Tendon Autograft

Abstract: Nowadays, several techniques are available for preserving the lateral aspect of the knee after meniscectomy; meniscus transplantation is the gold standard, and meniscus scaffold implantation is an effective alternative. However, meniscus transplantation is technically difficult and has many potential complications, whereas scaffolds resorb over time. Autografts are commonly used for labroplasty in shoulder and hip surgeries. We attempted to adapt this technique to the knee, using autografts for meniscus replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…However, with suitable intraarticular cartilage conditions a soft tissue graft could potentially serve well as a meniscus substitution as shown in the other cases in the present study. This is also in line with a recent case study that presented results from two cases, where the peroneus longus tendon was used as a meniscus transplant [25].…”
Section: Discussionsupporting
confidence: 89%
“…However, with suitable intraarticular cartilage conditions a soft tissue graft could potentially serve well as a meniscus substitution as shown in the other cases in the present study. This is also in line with a recent case study that presented results from two cases, where the peroneus longus tendon was used as a meniscus transplant [25].…”
Section: Discussionsupporting
confidence: 89%
“…There have been reports of meniscus reconstruction using the peroneus longus tendon after lateral meniscectomy [ 12 ]. In addition, a study using rabbits reported that the semitendinosus and gracilis were suitable for meniscus reconstruction [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Reconstruction of the lateral meniscus using the peroneus longus tendon has been performed after excision of the discoid lateral meniscus. 14 Moreover, studies using rabbits have reported that semitendinosis and gracilis are more useful for meniscal reconstruction. 15 Thus, reconstruction of the MM posterior root (MMPR) can be a useful technique for MMPRT.…”
Section: Introductionmentioning
confidence: 99%